Transformations in the Architecture of E-Groups: The Cases of Tikal and Uaxactun - Montuori, Riccardo (Restauro Compás y Canto S.A., 2021)
E-Groups are a unique typology in Maya architecture. These complexes consist of a central plaza delimited by a pyramidal building on the one side and by an elongated platform supporting three structures on the other side. Originated in Uaxactun, this denomination came from the nomenclature given to the first group ever identified with such characteristics. The interpretation of E-Groups began in 1924, with Frans Blom’s studies of what seemed to be a solar cycle observation complex. He observed that, looking from the pyramid, it was possible to see the alignment of the sun over the three structures to the east during the solstices and equinoxes. Several archaeological and archaeoastronomical studies have been carried out ever since, which have led to the formulation of different, sometimes even controversial hypotheses about their possible function. E-Groups’ buildings suffered various transformations over time, a very common practice in Maya architecture, which in many cases involved the filling and closure of pre-existing structures, later incorporated in the new building. The modifications that Maya builders brought about over time altered both the dimensions and the spatial relations between the buildings in these complexes, thus creating a complex superposition of constructive phases. In this paper, we analyze and compare, from an architectural point of view, the buildings of E-Groups in Mundo Perdido in Tikal and in Uaxactún, focusing on their constructive evolution.